The Central Elements of the Whistleblowing Legislations from Comparative Perspective - Deanoska - Trendafilova, Aleksandra (INSTITUTE FOR STRATEGIC RESEARCH AND EDUCATION - ISIE, 2018)
ABSTRACT In this paper, the focal subject of interest is the whistleblowing legislation method; precisely the elements each legislation needs to cover and elaborate in a clear, precise and detailed manner. That is conditio sine qua non, a prerequisite for efficient protection from corruption and human rights violations and deprivation. Without solid legal basis, the whistleblowers would not be adequately protected and this system would not be implemented or give expected results. The corruption is a serious and complex phenomenon that requires multifaceted methodological approach for fight against. It is especially met in areas of public interest, where education represents a part of. The author lists and explains the central elements that whistleblowing legislation has to cover, giving individual referral to several countries and their respective legal solutions. The researches proved that since the system is complex, a special law would be the best regulating method, but not necessarily. Namely, ill practice is noted in some of the countries assessed to have best legislation; and good practice and legislation has been detected in countries that regulate this issue not in a separate, but another legal act, usually the anti-corruption one. Further, the author elaborates the Macedonian legislation - both the law and the by-laws, concluding that it has all the necessary elements, but unfortunately still has not been implemented. In the concluding remarks, the author gives directions regarding the above-mentioned elements as well as recommendations for the necessary trainings that need to be performed for successful whistleblowers protection in practice.
Keywords: whistleblower, corruption, legislation, reporting, protection.